Romania : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses the following important issues related to the Romanian economy: inflation and inflation expectations, the need to bolster expenditure efficiency, minimum wage policy, and financial sector development. Headline inflation has decreased markedly in Romania in recent years. Key factors in this trend were oil and food price developments and, in particular, the recent reduction in the VAT rate. Romania has undertaken a strong fiscal consolidation since 2010, which reduced expenditure to among the lowest in the region. Minimum wages in Romania have risen sharply, which could directly affect wage distribution and improve income inequality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet